Effectiveness of Ginger and Honey in Massage Acupressure Point P6 (Nei Guan) to Emesis Gravidarum in First Trimester Pregnant Women in Indonesia 2024 - Rahayu Khairiah; Maya Puspita Sari; Sri Arlina Pujiastuti; Nonik Indra Sari; Ai Hayati; Kadang Ningsih; Nurul Fatimah; Rasti Puspitasari (Postgraduate, University of Mataram, 2024)
Emesis gravidarum, commonly known as morning sickness, often disrupts activities for pregnant women, primarily due to decreased progesterone levels and fluctuating hCG levels. A non-pharmacological approach to alleviate this condition involves acupressure massage at the P6 (Neiguan) point, combined with ginger juice and honey. This study aimed to assess the effectiveness of this method in reducing emesis gravidarum in Indonesian women during their first trimester. Utilizing a pre-experimental one-group pretest-posttest design, the research included 205 pregnant women experiencing first-trimester emesis gravidarum, selected through purposive sampling. Data collection was performed using the PUQE-24 questionnaire and observation sheets. The analysis, conducted with paired sample t-tests, revealed an average severity score reduction from 9.40 (moderate) to 4.49 (mild), showing a significant average difference of 4.91. The bivariate analysis confirmed the effectiveness of the intervention, with a p-value of 0.000. This method is recommended for health workers as it is cost-effective, has no side effects, and provides a safe treatment option for managing emesis gravidarum in pregnant women.